Application of Goal Setting to Increase Self Efficacy in Vocational Students: A Non Randomized Control Trial Approach (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
Self efficacy plays a very important role in learning activities. Self efficacy will encourage students to enjoy learning activities and maintain their attention on various tasks. One factor that is considered important in increasing self-efficacy is the existence of goal setting. This quasi-experimental study aims to obtain information on the application of goal setting in increasing self-efficacy. The subjects of this study involved 82 students who were divided into 2 groups, namely 41 treatment groups and 41 control groups. This type of research uses a non-randomized control trial method with a pretest & posttest control group design. The data collection technique used the adaptation scale of the self-efficacy questionnaire for children (SEQ-C) with a reliability of 0.88. The collected data was analyzed using the Independent Samples T-Test and Paired Samples T-Test. The results of this study inform that the application of goal setting has an impact on students' self-efficacy. So it can be seen that the treat group showed higher results compared to the control group.